2020
DOI: 10.1590/1678-992x-2018-0132
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and prediction of sulfuric acid digestion analyses data from PXRF spectrometry in tropical soils

Abstract: Sulfuric acid digestion analyses (SAD) provide useful information to environmental studies, in terms of the geochemical balance of nutrients, parent material uniformity, nutrient reserves for perennial crops, and mineralogical composition of the soil clay fraction. Yet, these analyses are costly, time consuming, and generate chemical waste. This work aimed at predicting SAD results from portable X-ray fluorescence (pXRF) spectrometry, which is proposed as a "green chemistry" alternative to the current SAD meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
(40 reference statements)
0
5
0
1
Order By: Relevance
“…P3 had a higher Si content compared with Al and Fe. Silva et al (2020) found lower contents of Fe 2 O 3 and TiO 2 and greater contents of SiO 2 in soils derived from gneiss compared to soils developed from itabirite, basalt, gabbro and tuffite. The Fe content varied less in the soils in upper and middle third of the landscape (P1=68,596; P2=75,160 mg kg -¹; values for Bo horizon), while in the lower third there was a drastic reduction (P3=53,297 mg kg -¹; Bo horizon).…”
Section: Soil Total Element Contents Obtained By Pxrfmentioning
confidence: 75%
“…P3 had a higher Si content compared with Al and Fe. Silva et al (2020) found lower contents of Fe 2 O 3 and TiO 2 and greater contents of SiO 2 in soils derived from gneiss compared to soils developed from itabirite, basalt, gabbro and tuffite. The Fe content varied less in the soils in upper and middle third of the landscape (P1=68,596; P2=75,160 mg kg -¹; values for Bo horizon), while in the lower third there was a drastic reduction (P3=53,297 mg kg -¹; Bo horizon).…”
Section: Soil Total Element Contents Obtained By Pxrfmentioning
confidence: 75%
“…Most prediction models were strongly influenced by texture. In tropical soils, the higher sand content tend to positively correlate with SiO 2 content, since this particle size fraction in most soils is dominated by quartz, composed by SiO 2 (Kämpf;Marques;Curi, 2012;Silva et al, 2019). Thus, the use of texture in SiO 2 (and in almost all the other) prediction models improved all statistical parameters evaluated in relation to models that did not use texture as an auxiliary variable.…”
Section: Models Validationmentioning
confidence: 83%
“…Also, relationships between the content of certain chemical elements and the different textural fractions of the soil can be made Weindorf;Zhang, 2011). In tropical soils, for instance, greater contents of SiO 2 tend to correspond to soils rich in quartz (SiO 2 ), dominantly found in greater contents in soils rich in sand (Kämpf;Maques;Curi, 2012;Silva et al, 2019).…”
Section: Variation Of Soil Elemental Contentsmentioning
confidence: 99%
“…Similar to Mmhg rocks, Sedimentary Siliciclastic rocks also predominantly consist of minerals that are highly resistant to chemical weathering, particularly quartz (Garzanti, 2019). This results in soils with lower clay contents and consequently lower oxide contents (Martins et al, 2005; L. S. Silva et al, 2019).…”
Section: Soils Clay Fraction Major Oxides Mapsmentioning
confidence: 99%
“…Despite the great importance of these oxides in the soil, few efforts are made to map them in the tropical regions of the world. This is due to the fact that laboratory methodologies are expensive, time consuming and have a high potential for environmental pollution (its quantification is performed by use of acid digestion with strong acids such as sulfuric acid), making difficult to obtain pedogenic oxides information for large areas, with high spatial resolutions (Silva et al, 2019). However, despite the great challenge of mapping the contents of these oxides, innovative techniques for digital soil mapping (DSM) can enable the construction of maps containing their contents with high spatial resolution and low levels of uncertainty, even with low sample densities (Mendes et al, 2022;Safanelli et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%